Diversity of Waterbirds in the Wetland of Pangpang Bay Essential Ecosystem Area, Banyuwangi, Indonesia - Fahrani, Elyn; Susintowati, Susintowati; Nugrahani, Magdalena Putri; Sungkono, Sungkono; Prasetyo, Yusuf Eko (Universitas Muhammadiyah Surakarta, 2024)
The Essential Ecosystem Area (KEE) of Teluk Pangpang, Banyuwangi is a wetland that is passed by the East Asia Australia Flyway (EAAF) bird migration route. This study aims to study the diversity, and abundance of waterfowl species, and the relationship between the existence of waterfowl species and environmental factors in each type of wetland habitat. This study was conducted in October 2023-January 2024 using the